1891 Minn. Gen. Stat. 517, § 6289 - (:unkn) unknown (My University, 1891)
§ 6289: Prohibited the sale or giving of any pistol or firearm to any minor under eighteen years. Violators guilty of a misdemeanor.
Keywords: TRANSFER - MINORS